Croatian Standardization of the Minnesota Multiphasic Personality Inventory-2 - Restructured Form (MMPI-2-RF) - Matešić, Krunoslav (Array, 2014)
MMPI-2-RF is the revised, shortened version of the MMPI-2, published in 2008 (University of Minnesota Press). It is composed of 338 true-false items selected from the MMPI-2 to reflect contemporary theories and models of psychopathology and personality. The MMPI-2-RF inventory is designed to assess clinically relevant variables and the advantage of this form of inventory is the smaller number of items and shorter administration time, compared to the MMPI-2 inventory. It is intended for testing persons over the age of 18. Administration usually takes 35 to 50 minutes. This revised form of inventory includes empirically valid scales which provide information about clinical symptoms, personality characteristics, behavior, interpersonal functioning and interests of the person being assessed. The objective of the study was to develop the Croatian edition of MMPI-2-RF inventory which will contain Croatian norms. The MMPI-2-RF normative sample is drawn from the MMPI- 2 normative sample and consists of 587 subjects (327 F and 260 M), aged 18 to 86, from all parts of Croatia. The inventory was administered individually and answers were combined in 51 scales: 9 validity scales, 3 Higher-Order Scales, 9 Restructured Clinical Scales, 23 Specific Problems Scales, 2 Interest Scales and 5 Personality Psychopathology Scales. Norms were calculated using linear and uniform T-scores, the same as in the U.S. standardization. The result of the standardization is the Croatian edition of the MMPI-2-RF inventory published by Naklada Slap in 2014. It is expectd that this version of the MMPI inventory will be very useful in a variety of situations: in clinics, in diagnosing mental disorders and in selecting appropriate treatment for every patient, helping clinicians in Croatia diagnose and treat patients.